2017
DOI: 10.15388/ekon.2017.2.10994
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors of Non-Performing Loans in Baltic and Scandinavian Countries: Lessons Learned in the Last Decade

Abstract: Abstract. A cross-country panel data regression was performed for non-performing loans (NPL) in Denmark, Estonia, Finland, Latvia, Lithuania and Sweden covering a period of years 1998-2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Evidently, inflation, which other authors did not consider, was observed to be a significant determinant impacting-on non-performing loans.Their findings show that inflation has a significantly negative relationship with nonperforming loans, thereby implying that during high inflation periods, the real burden of loan repayments decreases. In broad terms it means, that people are more likely to honor their obligations in the loan contract.Some authors segmented the non-performing loans between macro-variables and banking related variables,Kupčinskas and Paškevičius (2017). Findings here…”
mentioning
confidence: 89%
“…Evidently, inflation, which other authors did not consider, was observed to be a significant determinant impacting-on non-performing loans.Their findings show that inflation has a significantly negative relationship with nonperforming loans, thereby implying that during high inflation periods, the real burden of loan repayments decreases. In broad terms it means, that people are more likely to honor their obligations in the loan contract.Some authors segmented the non-performing loans between macro-variables and banking related variables,Kupčinskas and Paškevičius (2017). Findings here…”
mentioning
confidence: 89%
“…In the same year, Kupcinskas [15] examined the factors influencing NPLs in the Baltic and Nordic countries from 1998 to 2014. This research was conducted because during the global financial crisis from 2007 to 2008, increased NPL occurred in these countries.…”
Section: Literatur Reviewmentioning
confidence: 99%
“…Banks with high profitability showed an ability to create income, so they were less involved in offering risky loans [14]. Previous studies have shown that when ROA decreases, banks start investing in highrisk projects so that the level of NPL increases [9,[15][16][17][18]. The significant negative impact of ROA on non-performing loans shows that risk-taking is reduced in banks that show a high level of performance.…”
Section: Introductionmentioning
confidence: 99%
“…The first and foremost drawback is that there are high chances that the model is subjected to a degree of endogeneity. There is evidence that economic growth is one of the main determinants of NPL (109,(118)(119)(120) . Hence, there could exist reverse causality and simultaneity affecting the results of the model.…”
Section: Conclusion and Remarksmentioning
confidence: 99%